Subacute exposure to inorganic mercuric chloride (HgCI2) induce testicular toxicity in rats - PRAKASH, N; RAMKRlSHNA, V; PAWAR, ASHOK (The Indian Journal of Animal Sciences, 2013)
Investigation was carried out to determine the nature of testicular toxicity following subacute exposure to inorganic mercuric chloride (HgCI2) in rats. Adult male Albino rats were divided into 3 groups each consisting of 8 animals. Group I served as untreated control, group 2 were exposed to inorganic HgCl2 5 PPM through drinking water for 13 weeks. Group 3 animals served as recovery group following treatment similar to group 2. Body weight and haematocrit values were monitored at regular intervals. On sacrification, testis were removed and weighed and subjected to histopathological examination along with liver and kidney tissue samples. Testicular weight of rats exposed to inorganic HgCl2 (groups 2 and 3) signiticantly (P